Sosialisasi Dan Pendampingan Nomer Induk Berusaha: Untuk Meningkatkan Motivasi Berwirausaha Masyarakat Desa Talang Kabupaten Nganjuk - Kowi Akbar Prasetya; Bisyrul Kafi I. A.; Amanda Amelia S; Adelia Agatha Futti; Muhammad Imam Haramain; Hendra Maulana (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Business Identification Number (NIB) is an identification for a business entity adjusted to the line of business in the 2020 Indonesian Business Field Standard Classification, which is differentiated into types of economic activity that produce output aliases, both in the form of goods and services. A 13 digit business identifier containing a security and digital signature. The function of BIN is not only identity, but also business registration certificate, import identification number and customs access for companies engaged in the import and export business. The service activities carried out by KKNT 66 UPNVJT students aim to provide education as well as assistance for UMKM in Talang village, Nganjuk district with an understanding of the importance of registering a business on a Certified Identification Number. The hope of carrying out this service activity is to be able to provide motivation, self-confidence, and of course the progress of UMKM in Talang village. From this activity it can also be understood that there are still many business actors and UMKM who do not understand the existence and function of NIB. There are also those who are afraid to register their business for fear of being charged a large fee. Even though the existence of an NIB should be able to make it easier for UMKM players to develop their business.